(untitled) (Research, Society and Development, 2020)
Objectives: to investigate how the Systematization of Nursing Care in the practices of care to the parturients and puerperas during hospitalization and to create an educational website on the subject, in the methodology CIPE®. Methods: descriptive study. Participants were 75 students and 3 teachers from three undergraduate nursing courses located in the northwest of Rio Grande do Sul. Data collection was done through a questionnaire and analyzed through the thematic analysis. Results: all the respondents had had contact with the Systematization and / or the Nursing Process, but not all of them applied it to the practices of caring for the parturients and puerperas. To contribute to the teaching of Nursing Care Systematization, a website was developed that had positive appreciation on the part of the participants. Conclusion: the difficulties for the use and of the different methodologies can be overcome by the proximity of the nurses to the subject, be they teachers or assistance, a situation that reinforces the need for permanent education.